Evidence that a transcription factor regulatory network coordinates oxidative stress response and secondary metabolism in aspergilli. Issue 1 (1st January 2013) - Hong, Sung‐Yong; Roze, Ludmila V.; Wee, Josephine; Linz, John E.
Abstract The mycotoxin aflatoxin is a secondary metabolite and potent human carcinogen. We investigated one mechanism that links stress response with coordinate activation of genes involved in aflatoxin biosynthesis in Aspergillus parasiticus. Electrophoretic mobility shift assays demonstrated that AtfB, a basic leucine zipper (bZIP) transcription factor, is a master co‐regulator that binds promoters of early (fas‐1), middle (ver‐1), and late (omtA) aflatoxin biosynthetic genes as well as stress‐response genes (mycelia‐specific cat1 and mitochondria‐specific Mn sod) at cAMP response element motifs. A novel conserved motif 5′‐T/GNT/CAAG CCNNG/AA/GC/ANT/C‐3′ was identified in promoters of the aflatoxin biosynthetic and stress‐response genes. A search for transcription factors identified SrrA as a transcription factor that could bind to the motif. Moreover, we also identified a STRE motif (5′‐CCCCT‐3′) in promoters of aflatoxin biosynthetic and stress‐response genes, and competition EMSA suggested that MsnA binds to this motif. Our study for the first time provides strong evidence to suggest that at least four transcription factors (AtfB, SrrA, AP‐1, and MsnA) participate in a regulatory network that induces aflatoxin biosynthesis as part of the cellular response to oxidative stress in A. parasiticus.